N otes as A Picture of The Epistology Gene - Bekmurodovna, Yuldasheva Dilnoza (International Journal of Psychosocial Rehabilitation, 2020)
The article notes that the manuscripts are an epistolary genre, and the accuracy of the words, the fluency of ideas and opinions, without a doubt, is the beauty of written speech. The programs emphasize the internal speech of people: their thoughts, feelings, and feelings, expressing wishes, confessions and conclusions. It is recognized that the texts in the books are historic, and that psycholinguistic and cognitive-pragmatic research of these texts can provide a solid basis for the study of the rapidly growing textual linguistics and micromatin perceptions in world linguistics. In addition, there is a special recognition of poetic handwriting. Analyzes of manuscripts written in books by renowned scholars Poyon Ravshanov and Bekmurod Yuldashev. It is necessary to study the texts, to interpret and analyze them logically.